2020
DOI: 10.18203/2320-1770.ijrcog20204319
|View full text |Cite
|
Sign up to set email alerts
|

Classification of caesarean section based on Robson ten group classification system in our hospital

Abstract: Background: Recent data indicate that one in five women undergo caesarean section (CS). In the last decade, there has been a dramatic increase in the caesarean section rate worldwide, which now exceeds 30% in some regions. Thus, the increasing rate of caesarean section became a matter of international public health concern. Our study aimed to classify the CS-based on Robson ten group classification system (RTGCS) criteria which will subsequently enable us to standardise the indication of CS and establish proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…According to the Lebanese Ministry of Health, cesarean delivery rate was stable in Lebanon at 47% between 2011 and 2017. 16 Our high cesarean rates are comparable to those in the Dominican Republic (56.4%), 15 Egypt (52%), 9 and Iran (48%), 9 but higher than in India (34.5%), 17 Australia (23.5%), 18 Spain (19%), 19 and other Middle Eastern countries, such as Qatar (20%), Iraq (22%), and Saudi Arabia (21%). 9 Multiple studies reported that the major causes of the elevated cesarean section rate in Lebanon were related to: gestational age, multiple gestations, previous cesarean delivery, fetal malpresentation, parity, insurance status, and prenatal care site.…”
Section: Discussionmentioning
confidence: 71%
“…According to the Lebanese Ministry of Health, cesarean delivery rate was stable in Lebanon at 47% between 2011 and 2017. 16 Our high cesarean rates are comparable to those in the Dominican Republic (56.4%), 15 Egypt (52%), 9 and Iran (48%), 9 but higher than in India (34.5%), 17 Australia (23.5%), 18 Spain (19%), 19 and other Middle Eastern countries, such as Qatar (20%), Iraq (22%), and Saudi Arabia (21%). 9 Multiple studies reported that the major causes of the elevated cesarean section rate in Lebanon were related to: gestational age, multiple gestations, previous cesarean delivery, fetal malpresentation, parity, insurance status, and prenatal care site.…”
Section: Discussionmentioning
confidence: 71%